Addressing CPI resistance in NSCLC: targeting TAM receptors to modulate the tumor microenvironment and future prospects. Issue 7 (20th July 2022) - Peters, Solange; Paz-Ares, Luis; Herbst, Roy S; Reck, Martin
Abstract : Lung cancer remains a leading cause of cancer death worldwide, with non-small-cell lung cancer (NSCLC) accounting for the majority of cases. Immune checkpoint inhibitors (CPIs), including those targeting programmed cell death protein-1 and its ligand (PD-1/PD-L1), have revolutionized the treatment landscape for various cancers. Notably, PD-1/PD-L1 inhibitor-based regimens now form the standard first-line therapy for metastatic NSCLC, substantially improving patients' overall survival. Despite the progress made using CPI-based therapies in advanced NSCLC, most patients experience disease progression after an initial response due to resistance. Given the currently limited therapeutic options available for second-line and beyond settings in NSCLC, new treatment approaches are needed to improve long-term survival in these patients. Thus, CPI resistance is an emerging concept in cancer treatment and an active area of clinical research. Among the key mechanisms of CPI resistance is the immunosuppressive tumor microenvironment (TME). Effective CPI therapy is based on shifting immune responses against cancer cells, therefore, manipulating the immunosuppressive TME comprises an important strategy to combat CPI resistance. Several aspects of the TME can contribute to treatment resistance in NSCLC, including through the activation of Tyro3, Axl, MerTK (TAM) receptors which are essential pleiotropic regulators of immune homeostasis. Their roles include negatively modulating the immune response, therefore ectopic expression of TAM receptors in the context of cancer can contribute to the immunosuppressive, protumorigenic TME. Furthermore, TAM receptors represent important candidates to simultaneously target both tumor cells and immune cells in the TME. Clinical development of TAM receptor inhibitors (TAM RIs) is increasingly focused on their ability to rescue the antitumor immune response, thereby shifting the immunosuppressive TME to an immunostimulatory TME. There is a strong biological rationale for combining TAM RIs with a CPI to overcome resistance and improve long-term clinical responses in NSCLC. Combinatorial clinical trials of TAM RIs with CPIs are underway with encouraging preliminary results. This review outlines the key mechanisms of CPI resistance, including the role of the immunosuppressive TME, and discusses the rationale for targeting TAM receptors as a novel, promising therapeutic strategy to overcome CPI resistance in NSCLC.